Social Networks and Dynamic Firm Performance: Evidence from the Taiwanese Semiconductor Industry - Wang, Wei-Kang; Lu, Wen-Min Lu; Ting, Irene Wei Kiong; Chen, Yu-Hsuan (Universidad de Murci, 2021)
This study examines the relationship between board interlock and firm performance. Using the Taiwanese semiconductor industrys dataset from 2013 to 2015, this study uses centrality, structure holes, and the number of interlocking boards as proxies of board interlock. This study also evaluates firm performance over a long-term period through a dynamic data envelopment analysis model. which concluded that board interlock improves dynamic efficiency. Using a directors social network analysis, we also identified the top five companies with the best board interlock in terms of centrality, structural holes, and the number of interlocking directors. Overall, this paper is novel in linking board interlock to dynamic efficiency. The study enriches the extant accounting literature regarding the role of directors in influencing firm performance and evaluate firm performance from a multidimensional efficiency perspective.